DINAMIKA PENENTUAN ARAH KIBLAT MENGGUNAKAN ALAT KLASIK DAN MODEREN DI MASJID SULTAN ALAUDDIN MADANI - Saitul Mahtir; Muhammad Saleh Ridwan (HISABUNA: Jurnal Ilmu Falak, 2020)
Qibla direction is the direction in which all Muslims in all corners of the world look up and turn their faces to His Rab as the servant should be as a condition for the validity of prayer. The Qibla is in Mecca Al-Mukarramah which is in the form of a cube (Ka'bah). The direction of the Kaaba can be determined from any point or place on the surface of the earth with calculations and measurements. Therefore, calculating the Qibla direction is basically a calculation to find out in what direction the Kaaba in Mecca is seen from the surface of the earth. From this study discuss and test the accuracy of the Qibla direction at the Sultan Alauddin Madani Mosque using the classic and modern tools, the istiwa stick 'using the ball triangle method then juxtaposed with the shadow of the sun or the shadow of the Qibla direction. Then with a digital compass using the method of calculating the difference between Mecca and region (SBMD). Where istiwa 'is known as a tool that is not too urjen in society (traditional), while a digital compass maybe everyone already has it in an increasingly modern and sophisticated era like those in Android smartphones and other digital devices.